Effects of extra school-based physical education on overall physical fitness development - the CHAMPS study DK - Rexen, C. T.; Ersbøll, A. K.; Møller, N. C.; Klakk, H.; Wedderkopp, N.; Andersen, L. B. (Scandinavian Journal of Medicine & Science in Sports, 2015)
First, this study aimed to investigate if four extra physical education (PE) lessons per week improved children's development in physical fitness. Second, to investigate if the extra PE lessons improved development in physical fitness for children with lower levels of fitness at baseline. This study was a longitudinal controlled school-based study. The study population consisted of 10 Danish public schools with children in preschool to fourth grade (cohorts 0-4) with 2.5-year follow-up. Six schools had extra PE and four schools had normal PE. In total 1247 children were included (normal PE = 536, extra PE = 711). Development in fitness was analyzed using a composite z-score from six fitness tests. Multilevel mixed-effects linear regression was used to examine the association between school type and development in fitness. Extra PE increased the total development of composite z-score units among children enrolled in cohort 4 and borderline in cohort 3 with 1.06 (95% confidence interval 0.48-1.65) and 0.52 z-score units (-0.06 to 1.09), respectively. Children in the lower 50 percentiles increased their development with 0.47 (0.08-0.85) z-score units. Extra PE in schools improved development in fitness for cohort 4 and borderline for cohort 3 among all children. Extra PE improved fitness development across all cohorts among children with low fitness levels.